2020
DOI: 10.1123/jsr.2018-0157
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Instruction Reduces Patellofemoral Joint Loading During Bodyweight Squatting

Abstract: Context: The bodyweight squat exercise is a common component for treatment and prevention of patellofemoral pain; however, it can also place a high load on the patellofemoral joint. Restricting anterior motion of the knees relative to the toes during squatting appears to reduce patellofemoral loading. However, exercise professionals typically rely on verbal instructions to alter squat technique. Objective: To evaluate the influence of verbal instructions regarding squat technique on patellofemoral joint loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Both standing tests had different instructions and lead to different results. This indicates that the verbal instruction and the attempt to load evenly influence both the ipsilateral loading and WBS, which supports findings on this topic found in other populations and activities ( Milner et al, 2012 ; Almonroeder et al, 2020 ). This analysis only focused on two aspects of performance (i.e., ipsilateral loading and WBS) and is possible that there were differences across the tests that were not investigated as part of this study, such as those referring to muscle activity ( Lohse and Sherwood, 2012 ; Coratella et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…Both standing tests had different instructions and lead to different results. This indicates that the verbal instruction and the attempt to load evenly influence both the ipsilateral loading and WBS, which supports findings on this topic found in other populations and activities ( Milner et al, 2012 ; Almonroeder et al, 2020 ). This analysis only focused on two aspects of performance (i.e., ipsilateral loading and WBS) and is possible that there were differences across the tests that were not investigated as part of this study, such as those referring to muscle activity ( Lohse and Sherwood, 2012 ; Coratella et al, 2020 ).…”
Section: Discussionsupporting
confidence: 87%
“…The full text of 227 studies was retrieved and screened (figure 2). In total, 71 articles were included in the systematic review 25–95. There were 63 within-subject studies (56 healthy individuals, 7 patellofemoral pain), 1 randomised controlled trial in healthy individuals (online supplemental table 2) and…”
Section: Resultsmentioning
confidence: 99%
“…Wallace et al (9) reported peak patellofemoral joint force and stress magnitudes of approximately 1700 N (also similar to our force magnitudes) and 9.3 MPa (2–3 times greater than our magnitudes), respectively, during the bodyweight squat at 90° knee angle. Almonroeder et al (10) reported a mean patellofemoral joint force and stress magnitudes of approximately 2300 N and 11 MPa, respectively, while performing the bodyweight squat.…”
Section: Discussionmentioning
confidence: 99%